2002
DOI: 10.1002/pits.10046
|View full text |Cite
|
Sign up to set email alerts
|

Winning the battle and losing the war: Examining the relation between grade retention and dropping out of high school

Abstract: The aim of this investigation is to provide a comprehensive review of dropout research that examines grade retention within both associative and predictive models. A systematic review of seventeen studies examining dropping out of high school prior to graduation demonstrates that grade retention is one of the most powerful predictors of dropout status. The discussion addresses the discrepancies among the perspectives of many educational professionals regarding the effectiveness of grade retention and deleterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
181
1
28

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 273 publications
(222 citation statements)
references
References 34 publications
12
181
1
28
Order By: Relevance
“…To date, no study has examined the effect of grade retention in the early grades on children's peer-assessed liking. Several authors have speculated that negative effects associated with grade retention, such as behavioral problems and early school withdrawal, are the result, in part, of retained children experiencing peer stigmatization and discrimination (Alexander et al, 1994;Jimerson, Anderson, & Whipple, 2002). However, empirical support for these views is lacking.…”
Section: Developmental Significance Of Peer Relationsmentioning
confidence: 92%
See 1 more Smart Citation
“…To date, no study has examined the effect of grade retention in the early grades on children's peer-assessed liking. Several authors have speculated that negative effects associated with grade retention, such as behavioral problems and early school withdrawal, are the result, in part, of retained children experiencing peer stigmatization and discrimination (Alexander et al, 1994;Jimerson, Anderson, & Whipple, 2002). However, empirical support for these views is lacking.…”
Section: Developmental Significance Of Peer Relationsmentioning
confidence: 92%
“…Furthermore, we predicted that retained children would be perceived by peers and teachers as exhibiting higher academic competence in year 2, relative to promoted children. Finally, we tested a model that Consistent with developmental systems theory (Lerner, 1998), the well-established long-term effects of grade retention on school withdrawal (Alexander et al, 2003;Jimerson et al, 2002) are thought to be the result of multiple and interactive factors. However, research on the effects of grade retention has generally failed to investigate mediating processes by which retention alters children's transactions with their environment.…”
mentioning
confidence: 99%
“…Following a systematic review of the literature, Jimerson, Anderson, and Whipple (2002) concluded that grade retention was highly associated with high school dropout. Rumberger's (1995) analysis of data from the National Education Longitudinal Study of 1988 found that grade retention was the most powerful predictor of later dropout, with retained students being 11 times more likely to drop out of school.…”
Section: Grade Retentionmentioning
confidence: 99%
“…In a survey of 47 empirical studies with a variety of academic achievement measures, Holmes (1989) found that retained students scored 0.19 to 0.31 standard deviations below comparable students who had not been retained. A variety of studies have also found that retention is associated with an increased likelihood of dropping out (Jimerson et al, 2002;Roderick, 1994;Rumberger 1987). Furthermore, one of the primary criticisms of grade retention is that it disrupts a student's peer and cohort group, and potentially affects their socioemotional development (Fruehwirth, Navarro, & Takahashi, 2011;Shepard & Smith, 1990).…”
Section: The Policy and Practice Of Grade Retentionmentioning
confidence: 99%
“…There is considerable evidence that retention may have a negative impact on student achievement (Jimerson, 2001;Jimerson, Anderson, & Whipple, 2002;OECD, 2015;Shepard & Smith, 1990;Silberglitt, Jimerson, Burns, & Appleton, 2006). In a survey of 47 empirical studies with a variety of academic achievement measures, Holmes (1989) found that retained students scored 0.19 to 0.31 standard deviations below comparable students who had not been retained.…”
Section: The Policy and Practice Of Grade Retentionmentioning
confidence: 99%